Cooperative and Islamic Banks : What can they Learn from Each Other? - Al-Muharrami, Saeed (IMF Working Papers; Working Paper, 2013)
Islamic and cooperative banks such as credit unions are broadly similar in that they both share some risk with savers. However, risk sharing goes along with ownership control in cooperatives, whilst Islamic banks share risk with borrowers and downside risk with depositors. Islamic banking is consistent with mutual ownership, which may ease some of the governance and efficiency concerns implied by Shari'ah constraints. Greater risk sharing among cooperative bank stakeholders, using mechanisms embedded in Islamic financial products, may strengthen cooperatives' financial resilience.